Congenital cytomegalovirus infection: the state of the art and future perspectives - Salomè, S.; Corrado, F. R.; Mazzarelli, L. L.; Maruotti, G. M.; Capasso, L.; Blazquez-Gamero, D.; Raimondi, F. (Frontiers in Pediatrics, 2023)
Congenital cytomegalovirus (cCMV) infection is the most common congenital infection, affecting around 1 in 200 infants in high-income settings. It can have life-long consequences for up to one in four children, including sensorineural hearing loss and neurodisability. Knowledge about prevention, diagnosis and treatment increased in the recent years but some challenges remain. In this review we tried to summarize what is known both on obstetrical and pediatric sides and to point out controversial aspects and future perspectives. Awareness between general population and pregnant women should increase with specific information programs. Further research is needed to better defined classification at birth and long-term outcomes for so defined children. Finally, the opportunity for valaciclovir treatment during pregnancy, where appropriate, lead to evaluate a universal serological antenatal screening. A dedicated unit is advisable for better evaluation and management of both mothers and children.